BLUEPRINT MASA DEPAN INDUSTRI KREATIF YANG BERKELANJUTAN (EKOSISTEM, PONDASI ETIKA DAN EKONOMI, MENCETAKKAN VALUE JANGKA PANJANG) - Warisatun Ramadan; Alifudin Faturrachman; Minhajul Abidin; Faqih Ramdani Al Mubarak; Hadi Supratikta (Journal of Economic, Bussines and Accounting (COSTING), 2025)
The creative industry has emerged as a promising new pillar of economic growth; however, its long-term viability is fundamentally dependent on the integration of sustainability principles. This article presents a comprehensive blueprint structured around three core pillars: Adaptive Ecosystems, Balanced Ethical and Economic Foundations, and Long-Term Value Creation. Drawing on contemporary literature published between 2020 and 2025, as well as theoretical synthesis including Prof. Hadi Supratikta’s perspective on the critical role of Emotional and Spiritual Intelligence (EQ/SQ) in Society 5.0 this study identifies significant gaps between prevailing industry practices and global sustainability imperatives. The analysis highlights the urgent need to shift from linear economic models toward a Regenerative Economy, to institutionalize Environmental, Social, and Governance (ESG) standards, and to cultivate an ethically conscious creative workforce. The proposed blueprint advocates a holistic intervention approach, encompassing policies that promote green innovation, investment in ethics-based human capital development, and the establishment of standardized metrics for measuring social and cultural impact. Ultimately, this framework aims to ensure that the creative industry not only generates economic value but also functions as a positive and transformative force for society and the environment.